1999
DOI: 10.1093/brain/122.6.1147
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials in migraine patients: alterations depend on pattern spatial frequency

Abstract: Visual information is conducted by two parallel pathways (luminance- and contour-processing pathways) which are thought to be differentially affected in migraine and can be investigated by means of pattern-reversal visual evoked potentials (VEPs). Components and habituation of VEPs at four spatial frequencies were compared between 26 migraineurs (13 without aura, MO; 13 with aura, MA) and 28 healthy volunteers. Migraineurs were recorded in the headache-free interval (at least 72 h before and after an attack). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
97
4
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(125 citation statements)
references
References 38 publications
16
97
4
3
Order By: Relevance
“…As far as we know, only one study has reported lower first block amplitude in migraineurs (Afra et al, 1998). Two studies have reported increased first block amplitude in migraineurs (Oelkers et al, 1999;Sand et al, 2009), while most studies, including the present study, found no significant differences (Afra et al, 2000a;Coppola et al, 2007b;Coppola et al, 2011;Coppola et al, 2010b;Coppola et al, 2010a;Coppola et al, 2013b;Di Clemente et al, 2005;Oelkers-Ax et al, 2005;Ozkul and Bozlar, 2002;Sand and Vingen, 2000;Schoenen et al, 1995;Vigano et al, 2013;Wang et al, 1999).…”
Section: Visual Evoked Potential Amplitude In Migrainecontrasting
confidence: 64%
See 4 more Smart Citations
“…As far as we know, only one study has reported lower first block amplitude in migraineurs (Afra et al, 1998). Two studies have reported increased first block amplitude in migraineurs (Oelkers et al, 1999;Sand et al, 2009), while most studies, including the present study, found no significant differences (Afra et al, 2000a;Coppola et al, 2007b;Coppola et al, 2011;Coppola et al, 2010b;Coppola et al, 2010a;Coppola et al, 2013b;Di Clemente et al, 2005;Oelkers-Ax et al, 2005;Ozkul and Bozlar, 2002;Sand and Vingen, 2000;Schoenen et al, 1995;Vigano et al, 2013;Wang et al, 1999).…”
Section: Visual Evoked Potential Amplitude In Migrainecontrasting
confidence: 64%
“…Neither N70-P100 nor P100-N145 habituation measures were significantly different between groups. Independent confirmation of the habituation-deficit has been achieved only by two groups (Bednar et al, 2014;Ozkul and Bozlar, 2002), whereas it has not been confirmed in five studies by two other groups (Oelkers-Ax et al, 2005;Oelkers et al, 1999;Omland et al, 2013;Sand et al, 2009;Sand et al, 2008). In addition, lack of habituation was not observed in subset of migraineurs in study by a third group (Khalil et al, 2000).…”
Section: Habituation Measured By Visual Evoked Potentials In Migrainementioning
confidence: 95%
See 3 more Smart Citations